2005
DOI: 10.1080/03235400400027382
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thaumatin-like protein in transgenic tomato plants confers enhanced resistance toAlternaria solani

Abstract: A cDNA encoding thaumatin-like protein (TLP) from rice was cloned into the binary vector pMON410 under the control of the CaMV 35S promoter for Agrobacterium-mediated transformation of tomato. All putative transformants were tested for the integration and expression of the chimeric gene by polymerase chain reaction (PCR) for hygromycin resistance gene (hph) and enzyme-linked immunosorbent assay (ELISA) for TLP respectively. Constitutive, high-level expression of TLP was observed in transgenic plants. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Jayaraj et al 43 demonstrated that the purified 23 kDa rice TLP (TLP‐D34), expressed and purified through an Escherichia coli expression system, inhibited the mycelial growth of many fungi, including Fusarium graminearum and Curvularia lunata , the fungi associated with grain mold of sorghum. Furthermore, it has been demonstrated that transgenic crop plants overexpressing TLP have enhanced resistance against various pathogens 44–47. Vigers et al 33 reported the presence of a 22 kDa TLP (sormatin) in sorghum seeds cross‐reacting with zeamatin antiserum.…”
Section: Discussionmentioning
confidence: 99%
“…Jayaraj et al 43 demonstrated that the purified 23 kDa rice TLP (TLP‐D34), expressed and purified through an Escherichia coli expression system, inhibited the mycelial growth of many fungi, including Fusarium graminearum and Curvularia lunata , the fungi associated with grain mold of sorghum. Furthermore, it has been demonstrated that transgenic crop plants overexpressing TLP have enhanced resistance against various pathogens 44–47. Vigers et al 33 reported the presence of a 22 kDa TLP (sormatin) in sorghum seeds cross‐reacting with zeamatin antiserum.…”
Section: Discussionmentioning
confidence: 99%
“…Plant TLP mainly inhibits pathogenic and non-pathogenic fungi by lysing fungal spores, inhibiting spore germination, and reducing the vitality of young mycelium [ 4 , 5 ]. Recently, TLP genes were found to confer resistance to pathogenic fungi, including sclerotia, powdery mildew, and Pseudomonas syringae [ 6 , 7 ]. TLP transgenic plants can delay the development of a variety of fungal diseases and enhance plant resistance to pathogenic fungi [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…tomato (Lincoln et al ., ). Also, overexpression of a thaumatin‐like protein in transgenic tomato plants has been shown to confer enhanced resistance to A. solani (Radhajeyalakshmi et al ., ) and in a study in which genes coding for a maize β‐glucanase and a Mirabilis jalapa antimicrobial peptide were introduced into tomato, enhanced resistance to early blight disease was observed (Schaefer et al ., ).…”
Section: Introductionmentioning
confidence: 99%